Relasi Gramatikal Subjek Dalam Bahasa Karo - Karo, Marlisnawati Br; Mulyadi, Mulyadi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This research aims to look at the grammatical relations of subjects in the Karo language (BK) with a focus on testing subjects using the rules of raising, reflecting and anchoring. Through qualitative descriptive research methods, data was obtained from informants who are native BK speakers. The results of the analysis show that in BK intransitive clauses, the grammatical subject is located in the function of the only argument that follows the verb without an affix, whereas in transitive clauses, the grammatical subject is located in the agent argument. This research provides a deeper understanding of the nature of the subject's behavior in linguistic contexts, especially in regional languages such as BK, which can be an important contribution in enriching linguistic knowledge.